2013
DOI: 10.1177/0748233713500835
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal bioaccumulation in sediment, common reed, algae, and blood worm from the Shoor river, Iran

Abstract: Concentrations of 11 metals (cadmium, zinc, copper (Cu), vanadium (V), lead, magnesium (Mg), manganese, aluminum, iron (Fe), chromium (Cr), and nickel), and one metalloid (arsenic (As)) were measured in sediment, common reed (Phragmites australis), algae (Spirogyra sp.), and blood worm (Chironomus sp.) tissues of samples collected from the Shoor river. Samples were dried, acid digested, and the concentrations of metals were measured using inductively coupled plasma-optical emission spectrometer. A higher conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…In fact, the increasing use of antibiotics leads to the continuous release of them into the environment and their aggregation in various ecosystems can threaten human and animal health (Harrabi et al, 2018). The direct and indirect effects of many pollutants on different ecosystems and organisms have been well documented (Alavian Petroody, Hamidian, Ashrafi, Eagderi, & Khazaee, 2017;Hamidian, Razeghi, Zhang, & Yang, 2019;Hamidian, Zareh, Poorbagher, Vaziri, & Ashrafi, 2016;Khazaee et al, 2016;Majnoni, Rezaei, Mansouri, & Hamidian, 2013;Mansouri, Pourkhabbaz, Ebrahimpour, Babaei, & Hamidian, 2013;Mirzajani, Hamidian, Abbasi, & Karami, 2016;Mirzajani, Hamidian, Bagheri, & Karami, 2016;Norouzi, Mansouri, Hamidian, Ebrahimi, & Kardoni, 2012;Norouzi, Mansouri, Hamidian, Zarei, & Mansouri, 2012;Rajaei, Mansouri, Jahantigh, & Hamidian, 2012;Rezaei Kalvani, Sharaai, Manaf, & Hamidian, 2011;Taheri, Hamidiyan, & Khazaei, 2013), and various methods for their removal have been tested and implemented (Mojoudi, Hamidian, Goodarzian, & Eagderi, 2018;Mojoudi, Hamidian, Zhang, & Yang, 2019;Nekoei et al, 2009;Padashbarmchi, Hamidian, Zhang, et al, 2015;Veisi et al, 2010). There are still much to know about the detection, effects, and removal of antibiotics in terrestrial and especially aquatic environment.…”
Section: Reviewmentioning
confidence: 99%
“…In fact, the increasing use of antibiotics leads to the continuous release of them into the environment and their aggregation in various ecosystems can threaten human and animal health (Harrabi et al, 2018). The direct and indirect effects of many pollutants on different ecosystems and organisms have been well documented (Alavian Petroody, Hamidian, Ashrafi, Eagderi, & Khazaee, 2017;Hamidian, Razeghi, Zhang, & Yang, 2019;Hamidian, Zareh, Poorbagher, Vaziri, & Ashrafi, 2016;Khazaee et al, 2016;Majnoni, Rezaei, Mansouri, & Hamidian, 2013;Mansouri, Pourkhabbaz, Ebrahimpour, Babaei, & Hamidian, 2013;Mirzajani, Hamidian, Abbasi, & Karami, 2016;Mirzajani, Hamidian, Bagheri, & Karami, 2016;Norouzi, Mansouri, Hamidian, Ebrahimi, & Kardoni, 2012;Norouzi, Mansouri, Hamidian, Zarei, & Mansouri, 2012;Rajaei, Mansouri, Jahantigh, & Hamidian, 2012;Rezaei Kalvani, Sharaai, Manaf, & Hamidian, 2011;Taheri, Hamidiyan, & Khazaei, 2013), and various methods for their removal have been tested and implemented (Mojoudi, Hamidian, Goodarzian, & Eagderi, 2018;Mojoudi, Hamidian, Zhang, & Yang, 2019;Nekoei et al, 2009;Padashbarmchi, Hamidian, Zhang, et al, 2015;Veisi et al, 2010). There are still much to know about the detection, effects, and removal of antibiotics in terrestrial and especially aquatic environment.…”
Section: Reviewmentioning
confidence: 99%
“…Precisely when we analyse BSAF values for the tested heavy metals and chironomid larvae are we able to discern that they are very heterogeneous, both with respect to the absolute values obtained for individual elements in different studies, and in regard to the ratio of values between different elements. Thus, in the case of lead, BSAF was only 0.03 in the study of Reinhold, Hendriks, Slager and Ohm (1999) and was similar in the study of Hamidian, Zareh, Poorbagher, Vaziri and Ashrafi (2016), whereas in the study of Rezaei, Kamali and Shapoori (2011) the values of BASFBSAF for lead were significantly higher and ranged from 0.26 to 3.9. The situation is similar in the case of other elements.…”
Section: Resultsmentioning
confidence: 79%
“…Bonanno [23] also indicated that the trend of Ba contents in reeds was root > rhizome > leaf > stem. The accumulations of different metals in reeds are controlled by many factors such as specifi c physiological mechanisms, the concentrations and bioavailability of metals in the surrounding environment, and other physical/chemical environmental conditions [24][25][26]. One of the reasons that reeds can immobilize most toxic elements in the roots is to protect rhizomes, which are the only persistent part of the plant, thus less metals can be transferred from rhizomes to shoots [18].…”
Section: Resultsmentioning
confidence: 99%